The Correlation Between Students Engagement and Students Academic Achievement in Learning English at 11th Grade of MAN 4 Agam - Latifa, Annisa; Melani, Melyann; Reflinda, Reflinda; Roza, Veni (Pusdikra-Publishing.com, 2024)
This study was conducted to find out the correlation between students’ engagement and students’ academic achievement in learning English at 11th grade of MAN 4 Agam. This study used correlational design. The sample was the XI IPS 1 and 2 which consisted of 37 students which selected by using purposive sampling technique. Technique data collecting in this study was questionnaires and tests. The questionnaire was Student Engagement Instrument (SEI) consisted 33 questions and academic achievement test consisted 22 questions. In analyzing the data, this study used Pearson’s Product Moment in SPSS 20 version program. There were a strong positive correlation with a correlation coefficient of 0.669. This means that there is a significant relationship between these variables, showing that student engagement impacts academic achievement in various ways. So, higher student’ engagement is associated with higher learning achievement in English, whereas lower engagement corresponds to lower achievement.